A Conceptual Framework of Entrepreneurial Finance. (October 2019) - Clement, Tom; Silvernagel, Craig
This article proposes a framework and core content for entrepreneurial finance (EF) that distinguishes EF from corporate finance. The Realms of Entrepreneurial Finance (REF) framework builds on existing literature along with theories and methodologies from psychology and entrepreneurship. This study also offers a set of EF learning goals and objectives as well as suggestions for teaching EF. The REF framework benefits entrepreneurship educators and scholars in furthering the understanding, maturation, and legitimacy of EF education.